Penerapan Internet of Things Untuk Monitoring Kinerja Sensor Untuk Deteksi Dini Kebakaran - Ihsan, Ihsan; Armin, Armin; Aditya, Angga Wahyu (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2024)
Fire can happen anytime and anywhere without knowing it will happen. Fire incidents can cause significant losses, both material losses and human losses. Fires can occur due to various factors from electrical short circuits to individual negligence which can cause sparks that can result in the formation of a fire triangle that causes fire. This study aims to create an effective fire detection system by utilizing distributed multi-sensor technology in a microcontroller and then sent to the cloud so that it can be monitored in real time. The method in this research stage starts from needs analysis, design, implementation, integration & testing, verification, maintenance. The system built utilizes various sensors, namely the MQ135 smoke sensor, UVTron fire sensor, DS18B20 temperature sensor, BME280 air humidity sensor, wind speed and direction sensors. The data collected from these sensors is processed and then displayed via a web interface using the Laravel framework that can be accessed by users. The results of this study indicate that the system is able to provide effective and reliable early warning in potential fire situations.